Factors Affecting The Quality of Financial Reports in Local Governments (Study at the Gandus District Office, Palembang City South Sumatera Province) - Rizki Rahmadina Indra Putri; Lukita Tripermata; Andini Utari Putri (International Journal of Community Service & Engagement, 2023)
This study aims to determine the factors that affect the quality of financial reports in the government (Study at the Head Office of Gandus Sub-District, Palembang City, South Sumatra Province). The sample was selected using the Simple Random Sampling technique. Data from 30 respondents were collected through a questionnaire which was then analyzed using multiple linear regression. The results of this study prove that the competence of human resources, the regional financial accounting system, the use of information technology, government accounting standards, and internal controls affect the quality of financial reports. Simultaneously human resource competence, regional financial accounting systems, use of information technology, government accounting standards, internal control affect the quality of financial reports.